Characterisation of blood coagulation factor XIT475I - McVey, John H.; Lal, Kalpana; Imanaka, Yasufumi; Kemball-Cook, Geoffrey; Bolton-Maggs, Paula H. B.; Tuddenham, Edward G. D. (Thrombosis and Haemostasis, 2005)
PCR-SSCP and DNA sequence analysis of a factor XI (FXI) deficient patient (FXI:C 39 U/dL; FXI:Ag 27 U/dL) identified a C to T transition in exon 12 of the FXI gene (F11 c.1521C>T) that predicts the substitution of Thr475 by Ile (FXIT475I) within the serine protease domain of FXI. This mutation destroys a consensus sequence for N-linked glycosylation, N473-Y-T475, known to be utilized in vivo. The FXIT475I variant was generated by site-directed mutagenesis, together with other variants that could help explain the phenotype, and recombinant FXI variants were expressed in Chinese hamster ovary cells. FXI:Ag expression was analysed by Western blot analysis, ELISA and immunocyto-chemical staining. Wild-type FXI:Ag was secreted at high levels, however the mutant (FXIT475I) was secreted very poorly. Substitution of Thr475 by Ala, Pro, Lys or Arg (all of which abolish the glycosylation consensus sequence) also severely reduced the level of secreted FXI:Ag suggesting that glycosylation at Asn473 is required for folding or secretion. Concordant with this hypothesis the conservative substitution of Thr475 by Ser (which preserves the glycosylation consensus sequence) had no effect on FXI secretion. Thr/Ser475 is highly conserved in serine protease domains but the glycosylation site (Asn473) is not. Surprisingly, substitution of Asn473 by Ala (which removes the N-linked glycosylation site) had no effect on the levels of FXI:Ag secreted. In conclusion, although the FXI-T475I mutation destroys an N-linked glycosylation consensus sequence, the cause of failure to secrete FXI is not the loss of a glycosylation site but rather a direct effect of the substitution of this highly conserved residue.
Keywords: Factor XI; deficiency; mutation; glycosylation